Raw Materials, Technology, Healthcare Applications, Patent Repository and Clinical Trials on 4D Printing Technology: An Updated Review - Mohammad Sameer Khan; Sauban Ahmed Khan; Shaheen Shabbir; Md Umar; Sradhanjali Mohapatra; Tahir Khuroo; Punnoth Poonkuzhi Naseef; Mohamed Saheer Kuruniyan; Zeenat Iqbal; Mohd Aamir Mirza (MDPI AG, 2022)
After the successful commercial exploitation of 3D printing technology, the advanced version of additive manufacturing, i.e., 4D printing, has been a new buzz in the technology-driven industries since 2013. It is a judicious combination of 3D printing technologies and smart materials (stimuli responsive), where time is the fourth dimension. Materials such as liquid crystal elastomer (LCE), shape memory polymers, alloys and composites exhibiting properties such as self-assembling and self-healing are used in the development/manufacturing of these products, which respond to external stimuli such as solvent, temperature, light, etc. The technologies being used are direct ink writing (DIW), fused filament fabrication (FFF), etc. It offers several advantages over 3D printing and has been exploited in different sectors such as healthcare, textiles, etc. Some remarkable applications of 4D printing technology in healthcare are self-adjusting stents, artificial muscle and drug delivery applications. Potential of applications call for further research into more responsive materials and technologies in this field. The given review is an attempt to collate all the information pertaining to techniques employed, raw materials, applications, clinical trials, recent patents and publications specific to healthcare products. The technology has also been evaluated in terms of regulatory perspectives. The data garnered is expected to make a strong contribution to the field of technology for human welfare and healthcare.